2023
DOI: 10.3389/frsc.2022.1059312
|View full text |Cite
|
Sign up to set email alerts
|

The regional implications of just transition in the world's most coal-dependent economy: The case of Mpumalanga, South Africa

Abstract: IntroductionSouth Africa has had an extraordinarily heavy reliance on coal to fuel its economy, and it is one of the highest carbon dioxide emitters per capita globally. Current moves aligned with COP26 and recently announced Western support for a Just Transition Partnership to support decarbonisation in South Africa and replace coal fired power stations with renewables are to be welcomed. That said, the majority of South Africa's coal mines, thermal power stations and the currently important coal export indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…For example, 57% of businesses in Steve Tshwete local municipality offer services to either coal mines or coal plants (Semelane et al, 2021) and hundreds of small businesses rely on spending by direct and indirect coal workers (Pai et al, 2021). Globally, mining regions have generally struggled to cope with mine closure and the resulting economic loss, often leading to regional decline and effective town abandonment (Nel, Marais, and Mqotyana, 2023). Literature on regional resilience identifies key elements as strong local leadership, endogenous knowledge, innovation, willingness to change, experience from previous crises, access to funds, transferrable skills, and willingness to retrain, coupled with the availability of resources and market opportunities for a 'new' economy (ibid.).…”
Section: Local Implications and Considerationsmentioning
confidence: 99%
“…For example, 57% of businesses in Steve Tshwete local municipality offer services to either coal mines or coal plants (Semelane et al, 2021) and hundreds of small businesses rely on spending by direct and indirect coal workers (Pai et al, 2021). Globally, mining regions have generally struggled to cope with mine closure and the resulting economic loss, often leading to regional decline and effective town abandonment (Nel, Marais, and Mqotyana, 2023). Literature on regional resilience identifies key elements as strong local leadership, endogenous knowledge, innovation, willingness to change, experience from previous crises, access to funds, transferrable skills, and willingness to retrain, coupled with the availability of resources and market opportunities for a 'new' economy (ibid.).…”
Section: Local Implications and Considerationsmentioning
confidence: 99%
“…South Africa, for example, is facing a challenge of electricity supply and demand balance, resulting in power interruptions for several hours [11]. The country heavily relies on coal-fired power generation [12,13], which is experiencing operational challenges arising from aging infrastructure and insufficient maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…They found that support from federal policy was necessary to support structural change in these regions [15] . Nel et al drew on international and South African evidence of the effects and responses to mine closure, regional resilience theory and evolutionary economic geography theory to analyze the implications and prospects for economic renewal as the coal industry winds down [13] . In China, the majority of current research focuses on the barriers to and determinants of the industrial transformation of cities with coal resources.…”
Section: Introductionmentioning
confidence: 99%